Treasure island - "Stevenson, Robert Louis" (Oxford University Press: Karachi, 1997)
Jim Hawkins lives at an inn. One day, a sailor is killed there. In his bag, Jim finds a map of an island, which shows where pirates have hidden their gold. Jim goes with his friends to find the gold. But some of the sailors he chooses are pirates, who want the treasure for themselves. What can a boy do to stop Long John Silver and his pirates?
Keywords: Juvenile works-English